2018
DOI: 10.3390/en11092286
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Carbonization of Biosolids from Waste Water Treatment Plant

Abstract: The high moisture content of biosolid from a wastewater treatment plant limits its use for agriculture and energy applications. This limitation could be obviated by hydrothermal carbonization, which requires less energy compared to other thermochemical treatment processes, and results in stabilized solid hydrochar product. The present study examined this option by hydrothermally treating the biosolid at three temperatures (180, 200 and 220 °C) for 30 min, and at 200 °C for 15, 30 and 60 min. An increase of 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…b Yield (%) = (mass of each product/mass of feedstock) × 100, dry basis. -131 --a db = dry basis; TS = total solids of sludge feedstock; VM = volatile matter; FC = fixed carbon; HHV = higher heating value; references (Acelas et al, 2014;Afif et al, 2011;Ahn et al, 2020;Alatalo et al, 2013;Ali Shah et al, 2021;Amrullah and Matsumura, 2018;Anastasakis et al, 2018;Aragón-Briceño et al, 2017Becker et al, 2019;Berge et al, 2011;Bhatt et al, 2018;Biller et al, 2018;Breulmann et al, 2017;Brookman et al, 2018;Catallo and Comeaux, 2008;Chang et al, 2021;D. Chen et al, 2020;Chen et al, 2019Chen et al, , 2013bChen et al, , 2013aChu et al, 2020;Conti et al, 2020;Couto et al, 2018;  Results showed that WHSV between 1.5 and 3.1 hr -1 had no noticeable effect on co-HTG;  Co-HTG of MS with corn starch had slightly more H 2 and less CH 4 in gas composition than HTG of corn starch only;  Co-HTG resulted in less TOC yield than HTG of corn starch only.…”
Section: Declaration Of Competing Interestmentioning
confidence: 99%
“…b Yield (%) = (mass of each product/mass of feedstock) × 100, dry basis. -131 --a db = dry basis; TS = total solids of sludge feedstock; VM = volatile matter; FC = fixed carbon; HHV = higher heating value; references (Acelas et al, 2014;Afif et al, 2011;Ahn et al, 2020;Alatalo et al, 2013;Ali Shah et al, 2021;Amrullah and Matsumura, 2018;Anastasakis et al, 2018;Aragón-Briceño et al, 2017Becker et al, 2019;Berge et al, 2011;Bhatt et al, 2018;Biller et al, 2018;Breulmann et al, 2017;Brookman et al, 2018;Catallo and Comeaux, 2008;Chang et al, 2021;D. Chen et al, 2020;Chen et al, 2019Chen et al, , 2013bChen et al, , 2013aChu et al, 2020;Conti et al, 2020;Couto et al, 2018;  Results showed that WHSV between 1.5 and 3.1 hr -1 had no noticeable effect on co-HTG;  Co-HTG of MS with corn starch had slightly more H 2 and less CH 4 in gas composition than HTG of corn starch only;  Co-HTG resulted in less TOC yield than HTG of corn starch only.…”
Section: Declaration Of Competing Interestmentioning
confidence: 99%
“…This property is common to industrial organic wastes of interest such as agrifood, paper, and woodcrafts. Therefore, a drying step is required [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since the HTC process proceeds in a closed system, the phase change of the moisture does not occur so consequently the latent heat of vaporisation is not utilized in the process [88]. It requires less energy compared to other thermochemical treatment processes, and results in a stable solid product [89]. The hydrothermal process is characterized by high liquid yields, as its content is very high at the start of the process and almost does not change.…”
Section: Hydrothermal Carbonisationmentioning
confidence: 99%